Level of knowledge of educational robotics in a Peruvian university - Guerrero Támara, Vidal; Penadillo Lirio, Rudecindo Albino; Lezameta Blas, Úrsula (Rastros Rostros, 2021)
The objective of this research work was to analyze the level of knowledge of educational robotics in a Peruvianuniversity. The study corresponds to a quantitative approach and due to its level of depth was descriptive. Thenon-experimental cross-sectional design was used. The sample was non-probabilistic census type, consistingof 35 teachers from the Academic Department of Education. Information was collected through a questionnaire with content validity through expert judgment and a reliability of 0.89. The data were processed with theMicrosoft Excel 2019 spreadsheet and the hypothesis was contrasted with the proportion test with a confidence level of 95%. It is concluded that 97% of teachers do not of the conceptual foundations of educationalrobotics, while 94% lack knowledge of the pedagogical aspects of educational robotics. On the other hand, 74%of teachers do not have knowledge of the application of educational robotics. These results show a low level ofknowledge about educational robotics in teachers